ANALISIS IMPLEMENTASI KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU - banamtuan, maglon ferdinand (Jurnal Dinamika Pendidikan, 2020)
The objectives achieved in this study are: 1). Describe and analyze the implementation of the zoning system policy in the Admission of New Students in the State Senior High School 1 Kupang; 2). Identifying and describing the obstacles found in the implementation of the zoning system policy in the Acceptance of New Students at State Senior High School 1 Kupang; and 3). Want to know the advantages and disadvantages of the implementation of the zonesi system in the acceptance of new students in the State Senior High School 1 Kupang. Then the results of the research found are: 1). These four things will affect the level of success and failure of implementing a policy, namely: a). Communication; b). Resource; c). Disposition; and D). organizational structure. 2). The participation shown by the Kupang State High School 1 stakholder is: a). Providing opportunities to the surrounding community; b). Transportation cost savings; and c). Reduces jams